2018
DOI: 10.1016/j.micron.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A study of interface reaction zone in a SiC fibre/Ti-17 composite

Abstract: The interface reaction zone (RZ) in a unidirectional continuous carbon-coated SiC fibre reinforced Ti-17 titanium alloy composite is investigated. Micro-computed tomography (CT), scanning and transmission electron microscopy are employed to characterize the fibre/matrix interface. It is revealed that the interface RZ is a 400 nm thick titanium carbide (TiC) layer which is composed of two sublayers, a 60 nm thick fine-grained sublayer and an approximate 340 nm thick coarse-grained sublayer. The RZ is formed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The interfacial RZ in this composite system was thoroughly investigated elsewhere. 56 It is found that the interface debonding occurred between fibre coating and the reaction zone. This suggests that the bond between C coating and reaction zone is the weakest compared with those formed between different layers at the interface, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interfacial RZ in this composite system was thoroughly investigated elsewhere. 56 It is found that the interface debonding occurred between fibre coating and the reaction zone. This suggests that the bond between C coating and reaction zone is the weakest compared with those formed between different layers at the interface, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the voids is related to the diffusion process controlling chemical reaction at the interface. As discussed in, 56 the carbon atoms in the carbon coating diffused across the initially formed fine-grained sublayer into the contact area to interact with the atoms migrating from the matrix into the contact area during composite fabrication. In such situation, the outflow of the carbon atoms led to the formation of voids at the interface of the carbon coating and the RZ, as shown in Figure 8.…”
Section: Resultsmentioning
confidence: 99%
“…It has been noted that the RZ at the fiber/matrix interface is composed of three sublayers in the composites after isothermal exposure at 450, 650, 800, and 900 for up to 100 h. The fine-grained sublayer and coarse-grained sublayer are inherited from the RZ formed in the as-fabrication composite. Both remained untransformed in the process of isothermal exposure and are TiC-type titanium carbides (Fan & Zhou, 2018). Those carbides in the initially formed sublayers do not interact with the matrix since the minimum temperature for the interaction between the carbides and Ti is 1,300°C (Strashinskaya, 1971), which is much higher than the isothermal exposure temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical reaction occurring during composite fabrication and isothermal exposure at 450, 650, and 800°C can be described by equation (1), which explains the formation of the TiC-type carbide, although the short-range ordered carbide can exist from TiC 0.48 to TiC 1.0 due to the variation of diffusivities of the C and Ti atoms. The reactions associated with the formation of the titanium carbide are discussed in detail elsewhere (Fan & Zhou, 2018). In brief, disordered TiC x is only stable at temperatures above 820°C, but the disordered state can exist below 720°C as a metastable state if the material is rapidly quenched (Lipatnikov et al, 1998, 2000; Zueva & Gusev, 1999; Korzhavyi et al, 2002).…”
Section: Resultsmentioning
confidence: 99%